Potassium‐Ion Storage in Cellulose‐Derived Hard Carbon: The Role of Functional Groups. Issue 9 (8th July 2020) - Nanjundan, Ashok Kumar; Gaddam, Rohit Ranganathan; Farokh Niaei, Amir H.; Annamalai, Pratheep K.; Dubal, Deepak P.; Martin, Darren James; Yamauchi, Yusuke; Searles, Debra J.; Zhao, Xiu Song
Abstract: Potassium‐ion storage is being explored by researchers for its advantages in forming graphite‐based intercalation compounds, with cost‐effective production compared to lithium‐ion systems. However, its poor performance in graphite‐based platforms, owing to the volume expansion required for intercalation, has demanded alternative materials for reversible potassiation. Herein, we demonstrate a simple one‐step pyrolysis approach to develop an amorphous hard carbon material from commercial cellulose for high‐performance potassium‐ion batteries (KIB). The larger interlayer spacing (∼0.4 nm) alongside the electronegative oxygen functional groups promotes potassium‐ion storage. High capacity, good rate and long cycling performance with lower‐volume expansion could be credited to the amorphous carbon that possesses turbostratic nanodomains. Further, oxygen functional groups on the carbon material are identified in our experimental studies, and density functional theory simulations indicate that these are likely to enhance the potassium‐ion capacity of the materials. Abstract : Functional choice : Potassium ion‐storage in biomass‐derived hard carbon, which can offer potential alternative cost‐effective batteries, is less understood in terms of processing and structural requirements. Here, the use of vegetable fibres‐derived cellulose for producing hard carbon with surface functionalities is demonstrated. With density functional theory mechanical modelling calculations, it also demonstrates the tailorability and role of oxygen‐containing functional groups present in hard carbon for efficient potassium‐ion storage.